(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Comparative literature is the process of studying different literary works by comparing their authors, styles, themes, and cultures. This approach occupies an important place in literary studies and has a number of implications. Through comparative literature, the interaction between different cultures can be studied. Every culture has its own values, traditions and customs. Identifying these differences and similarities with the help of comparative analysis helps to develop intercultural communication. For example, studying the differences between Eastern and Western literatures can enhance mutual understanding. Comparative literature allows for a deeper study of literary styles and genres. Different authors use different styles in their works. By comparing them, it is possible to observe the development process of literature, the emergence of new styles, and how old styles change. It is an important source of information for literary scholars. Comparative literature helps to understand the historical context. Every literary work depends on the social, political and cultural conditions of its time. Historical processes, changes and social problems can be determined by comparing literary works of different periods. This is important for historical research. Comparative literature helps to study human nature. Different authors express the inner world, feelings and relationships of a person in different ways. By comparing them, it is possible to determine the common aspects and differences of human nature.